„Bei dir läuft“ - Neuer Sinn in der Zeit und die migrationsgesellschaftliche Verhandlung des Normverstoßes in der Jugendsprache - Büttner, Denise; Frank, Magnus (Symbolische Ordnung und Bildungsungleichheit in der Migrationsgesellschaft. Interkulturelle Studien)

Die sozial-religiösen Gesprächskreise der „Gülen-Bewegung“. Eine praxeologische Skizze zur Institutionalisierung eines islamischen Bildungsverständnisses - Geier, Thomas; Frank, Magnus; Büttner, Denise (Kulturen der Bildung)

Higher order time discretizations with ALE finite elements for parabolic problems on evolving surfaces - Kovács, Balázs; Power Guerra, Christian Andreas (IMA Journal of Numerical Analysis)
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Error analysis for full discretizations of quasilinear parabolic problems on evolving surfaces - Kovács, Balázs; Power Guerra, Christian Andreas (Numerical Methods for Partial Differential Equations)
Keywords: Applied Mathematics; Computational Mathematics; Numerical Analysis; Analysis

A-Stable Time Discretizations Preserve Maximal Parabolic Regularity - Kovács, Balázs; Li, Buyang; Lubich, Christian (SIAM Journal on Numerical Analysis)
Keywords: Numerical Analysis; Applied Mathematics; Computational Mathematics

Numerical analysis of parabolic problems with dynamic boundary conditions - Kovács, Balázs; Lubich, Christian (IMA Journal of Numerical Analysis)
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

A Parallel Numerical Solution Approach for Nonlinear Parabolic Systems Arising in Air Pollution Transport Problems - Karátson, J.; Kovács, Balázs (Mathematical Problems in Meteorological Modelling)

p-adic L-functions for Rankin–Selberg convolutions over number fields - Januszewski, Fabian (Annales mathématiques du Québec; Special Issue in Honor of Glenn Stevens)
Keywords: General Mathematics

On Period Relations for Automorphic L-functions II - Januszewski, Fabian (arXiv:1604.04253)
We study Hecke algebras for pairs $({\mathfrak g},K)$ over arbitrary fields $E$ of characteristic $0$, define the Bernstein functor and give another definition of the Zuckerman functor over $E$. Building on this and the author's previous work on rational structures on automorphic representations, we show that hard duality remains valid over $E$ and apply this result to the study of rationality properties of Sun's cohomologically induced functionals. Our main application are period relations for the special values of standard $L$-functions of automorphic representations of $GL(2n)$ admitting Shalika models.

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (2016 IEEE International Conference on Communications (ICC))

Ziehen und Beweisen mit DGS - Welche Beweiskraft haben für Studierende die Erkenntnisse, die sie im Zugmodus gewinnen? - Werth, Gerda (Beiträge zum Mathematikunterricht)

Regiere dich selbst - Hälterlein, Jens

Mundus pictus. Die bildliche Darstellung astronomischer und geographischer Strukturen in komputistischen Handschriften des 9. Jahrhunderts?! - Englisch, Brigitte (Proceedings of the 6. International Conference on the Science of Computus in Ireland and Europe, Galway 7-11 July, 2016)

Mappa mundi - Die St. Galler Kartentradition des frühen Mittelalters - Englisch, Brigitte

Zusammenhänge zwischen Sprachkompetenz und verstehensorientierter Leistung beim Umgang mit Brüchen - Wessel, Lena; Wilhelm, Nadine (Beiträge zum Mathematikunterricht 2016)

Is grade 7 too late to start with bilingual mathematics courses? An intervention study - Wessel, Lena; Prediger, Susanne; Schüler-Meyer, Alexander; Kuzu, Taha (TSG 32 at 13th International Congress on Mathematical Education, Hamburg, July 2016)

Writer’s overload: A multifaceted concept and its clarification - Karsten, Andrea; Scharlau, Ingrid; Klingsieck, Katrin B. (die hochschullehre)

Gerhard Ackermann, In Acht und Bann: Lic. Johannes Ackermann (1900-1942), Leipzig 2015 - Janus, Richard (Jahrbuch zur Westfälischen Kirchengeschichte)

Amos - Janus, Richard; Kirsner, Inge

The Wittenberg-Constantinople Negotiations in the 16th and 17th Century. A Form of Early Ecumenical Dialogue? - Janus, Richard (Synthesis)